The determinants of Islamic Banking profitability in Malaysia / Aini Ruwaida Ahmad Nor Komar and Nur Izyan Mohd Aziz - Ahmad Nor Komar, Aini Ruwaida; Mohd Aziz, Nur Izyan (Faculty of Business Management, 2016)
This study conducted the determinants of the Islamic banking profitability in Malaysia. 9 samples of Islamic banks with 8 years financial data will be chosen to participate in this research. This study focuses on the 9 Islamic banks which are Bank Islam Malaysia Berhad, Bank Muamalat Berhad, Affin Islamic Bank Berhad, CIMB Islamic Bank, Maybank Islamic Bank, Kuwait Finance House, RHB Islamic Bank and Al-Rajhi Bank also Hong Leong Islamic Bank. It is because these companies have long been established and also active in the industry. The purpose of this paper is to closely examine the most influence factors that affect Islamic banking profitability. It is also to examine the relationship between the variables. This will be seen on the variables which are asset quality, bank size, financial risk and liquidity. Some tests have been run in order to get the result of the relationship between the dependent variable and independent variable. Therefore, the result shows that all the variables are insignificant but only one is positively relationship affects Islamic bank profitability which is bank size.